Bcl‐2 hijacks the arsenic trioxide resistance in SH‐SY5Y cells. Issue 2 (14th December 2021) - Wang, Jinling; Peng, Xiaohui; Yang, Daowei; Guo, Mengyu; Xu, Xiao; Yin, Fengyue; Wang, Yu; Huang, Jiaqing; Zhan, Linghui; Qi, Zhongquan
Abstract: Aresenic trioxide (ATO) is proven to be active against leukaemia cells by inducing apoptosis and differentiation. Even though ATO could effectively induce remissions of leukaemia cells, the drug resistance was observed occasionally. To further dissect the mechanism of ATO resistance, we selected the ATO‐resistant SH‐SY5Y cells and found that Bcl‐2 controlled the sensitivity of ATO in SH‐SY5Y cells. We report that necroptosis, autophagy, NF‐ƘB and MAPK signalling pathway are not involved in ATO‐induced apoptosis. Moreover, the ATO‐resistant cells showed distinct mitochondrial morphology compared with that of ATO‐sensitive cells. Intriguingly, nude mice‐bearing ATO‐sensitive cells derived xenograft tumours are more sensitive to ATO treatment compared with that of ATO‐resistant cells. These data demonstrate that cancer cells can acquire the ATO‐resistance ability by increasing the Bcl‐2 expression.